Giant anogenital condyloma in 12-year-old-girl victim of sexually abused: a case report - Pereira, Araiz C.C.; Menezes, Maria Luiza B.; Barros, Romualda C.R.; Maia, Angelina F.; Carmo, Deyse S. (Brazilian Journal of Sexually Transmitted Diseases, 2008)
Adolescent, 12 years old, with warts in vulva for seven months, pain and fetid odor after use of podofilina three days ago. Repetitive sexual abuse. Treatment for syphilis four months ago with a single dose of benzatin penicilin. On examination: extensive condyloma in vulva, perineum and peria nal, with areas of necrosis, purulent discharge and fetid odor. Hypochromic stain on the skin, crusts on members and trunk. Diagnostic hypotheses: giant condyloma infected anogenital and secondary syphilis associated with piodermitis. Clinical and syndromic treatment were done for secondary syphilis, with coverage to secondary infection and cervicitis. Imiquimod was used for treatment of condyloma, with excellent clinical outcome.